Effect of Micronutrients on Fruit Set, Fruit Retention and Yield of Her (Zi7SPhus mauritiana Lamk - Kamble, A B; Desai, U T; Choudhari, S M (Annals of Arid Zone, 2016)
Studies on foliar applications of Fe, Zn, Mn, B in ber revealed that all nutrients increased flower clusters, shoot-I; fruit set, fruit retention, fruit wight and yield. ZnS04 at 0.4%, FeS04 at 0.4% and boric acid at 0.2% gave best results when sprayed in August-September. Application in July or October were not useful to increase yield.